Circadian rhythm and pain: a modeling using multiagent systems - dos Santos, Angélica T.; Machado, Catia M. S.; Adamatti, Diana F. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2018)
The circadian rhythm is responsible for the daily routines without metabolism and its disorders have great repercussion, such as obesity and mental disorders. This study is, the work approach has metate the study of synchronization and synchronization cycle circadian and influenced the variable of the, in the perspective of an integrated system with an computational system and computational. Results show the circadian rhythm periodicity is modified by the pain variable.